2020
DOI: 10.3390/agronomy10091284
|View full text |Cite
|
Sign up to set email alerts
|

How Can Weedy Rice Stand against Abiotic Stresses? A Review

Abstract: Weedy rice is one of the most common weeds in rice cultivation in many rice areas throughout the world and it is able to cause significant yield reductions. Weedy rice is characterized by a high biological diversity that permits different populations to be identified on the basis of their morphological and physiological traits. This variability contributes to its success in different environments and allows different abiotic stresses, which are intensified by climate change, to be faced. Taller plants, enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 123 publications
0
10
0
Order By: Relevance
“…This study highlighted that Baldo performed better under high salt concentrations than CL80; thus the availability of salt-tolerant rice varieties is particularly important, as the majority of the rice areas throughout the world are located near coastal areas and river deltas where salinity problems are more common (Formentin et al 2018). Moreover, some weeds can be more competitive than others in saline environments (Fogliatto et al 2020); according to our study, E. crus-galli is favored more than O. sativa under saline conditions, and thus more efforts should be made to control this weed. Populations resistant to ALS inhibitors showed variable behavior, with some populations that tolerate salt (such as the E. crus-galli r1 population) and others that can be more sensitive to salt (such as the E. crus-galli population r2 and the CL80 rice variety).…”
Section: Populationmentioning
confidence: 96%
See 2 more Smart Citations
“…This study highlighted that Baldo performed better under high salt concentrations than CL80; thus the availability of salt-tolerant rice varieties is particularly important, as the majority of the rice areas throughout the world are located near coastal areas and river deltas where salinity problems are more common (Formentin et al 2018). Moreover, some weeds can be more competitive than others in saline environments (Fogliatto et al 2020); according to our study, E. crus-galli is favored more than O. sativa under saline conditions, and thus more efforts should be made to control this weed. Populations resistant to ALS inhibitors showed variable behavior, with some populations that tolerate salt (such as the E. crus-galli r1 population) and others that can be more sensitive to salt (such as the E. crus-galli population r2 and the CL80 rice variety).…”
Section: Populationmentioning
confidence: 96%
“…The effects of salinity on cultivated plants can be intensified by the presence of other limiting factors, such as competition due to the presence of weeds, which are in general less susceptible to environmental stresses than crops, as they are more adaptable to changes (Fogliatto et al 2020;Korres et al 2016). The higher tolerance of weeds to environmental changes is mainly related to the fact that wild species have not undergone the same level of selection to obtain advantageous traits (Korres et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, its competitive ability is higher than crop, because it is taller and then more able to capture light, and it has a higher nutrient efficiency (especially for nitrogen use). It is also reported that weedy rice can tolerate stress conditions better than the current cultivars [21,26]. In addition, weedy rice develops several strategies in order to escape to its management.…”
Section: Biological Features and Competitive Ability Of Weedy Ricementioning
confidence: 99%
“…weed hoeing) that can be problematic for the presence of water in the field (Chauhan, 2012). However, other techniques are already in use as an integration to chemical weed control in conventional rice production or as the only available tools in organic farming (Fogliatto et al, 2020b). Among these, the use of false seedbed technique, a good soil levelling, to obtain a uniform water depth, and rice transplanting, to favour earlier and faster rice growth compared to weeds, are the most widespread (Dass et al, 2017;Shekhawat et al, 2020).…”
Section: Introductionmentioning
confidence: 99%